Persepsi Konsumen Atas Kualitas Layanan, Kualitas Produk, dan Harga terhadap Loyalitas Pelanggan Caffe Legend Jogja - Unmehopa, Yosina Weisemina; Jemadi, Jemadi (Universitas Proklamasi 45, 2024)
Caffe Legend Jogja which was present in 2012. Where the development is very rapid with the number of visits that continues to grow, many aspects of Caffe Legend Jogja are required to improve the quality of service, product quality, and price, these three aspects can create customer loyalty. The purpose of this study is to find out whether there is an influence of service quality on customer loyalty to Caffe Legend Jogja, whether there is an influence of product quality on customer loyalty to Caffe Legend Jogja, whether there is an influence of price on the loyalty of Caffe Legend Jogja customers, whether there is an influence on service quality, product quality, prices simultaneously on customer loyalty of Caffe Legend Jogja. The respondents in this study were all 100 people from Caffe Legend Jogja. This study used the saturated sample method, which is a sample determination technique when all members of the population are used as samples. The method used is multiple linear analysis. The results of this research showed that the quality of services and product quality did not have a significant effect on customer loyalty, partially. Otherwise, the price has a significant effect on customer loyalty, partially. The result of this research also showed that the quality of services and the price have a significant effect on customer loyalty at Caffe Legend Jogja, simultaneously.